Are hospitals ready to response to disasters? Challenges, opportunities and strategies of Hospital Emergency Incident Command System (HEICS) - Yarmohammadian, M.; Atighechian, G.; Shams, L.; Haghshenas, Abbas (Isfahan University of Medical Sciences, 2011)
BACKGROUND: Applying an effective management system in emergency incidents provides maximum efficiency with using minimum facilities and human resources. Hospital Emergency Incident Command System (HEICS) is one of the most reliable emergency incident command systems to make hospitals more efficient and to increase patient safety. This research was to study requirements, barriers, and strategies of HEICS in hospitals affiliated to Isfahan University of Medical Sciences (IUMS).METHODS: This was a qualitative research carried out in Isfahan Province, Iran during 2008-09. The study population included senior hospital managers of IUMS and key informants in emergency incident management across Isfahan Province. Sampling method was in non-random purposeful form and snowball technique was used. The research instrument for data collection was semi-structured interview; collected data was analyzed by Colaizzi Technique. RESULTS: Findings of study were categorized into three general categories including requirements (organizational and sub-organizational), barriers (internal and external) of HEICS establishment, and providing short, mid and long term strategies. These categories are explained in details in the main text. CONCLUSIONS: Regarding the existing barriers in establishment of HEICS, it is recommended that responsible authorities in different levels of health care system prepare necessary conditions for implementing such system as soon as possible via encouraging and supporting systems. This paper may help health policy makers to get reasonable framework and have comprehensive view for establishing HEICS in hospitals. It is necessary to consider requirements and viewpoints of stakeholders before any health policy making or planning.